2002
DOI: 10.1359/jbmr.2002.17.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular and Psychomotor Function in Elderly Subjects Who Fall and the Relationship With Vitamin D Status

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
189
4
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(214 citation statements)
references
References 26 publications
(27 reference statements)
14
189
4
7
Order By: Relevance
“…The low D-hormone serum levels observed with a creatinine clearance of <65 ml/min may also be one reason for the increased osteopenia and osteoporosis observed with low creatinine clearance by other authors [15,16]. Our result enhances the theory suggested by other studies [4,5,6,7,17,18,19,20,21,22] that D-hormone is an independent risk factor for falls [1,2,5,23], and that D-hormone is directly involved in the causal pathogenic pathway of decreased muscle strength related falls [9,23,24]. It has been recently confirmed in VDR gene deleted mice that the absence of VDR causes muscle abnormality independently of secondary metabolic changes, e.g.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The low D-hormone serum levels observed with a creatinine clearance of <65 ml/min may also be one reason for the increased osteopenia and osteoporosis observed with low creatinine clearance by other authors [15,16]. Our result enhances the theory suggested by other studies [4,5,6,7,17,18,19,20,21,22] that D-hormone is an independent risk factor for falls [1,2,5,23], and that D-hormone is directly involved in the causal pathogenic pathway of decreased muscle strength related falls [9,23,24]. It has been recently confirmed in VDR gene deleted mice that the absence of VDR causes muscle abnormality independently of secondary metabolic changes, e.g.…”
Section: Discussionsupporting
confidence: 87%
“…D-hormone has a scientifically established effect on muscle strength, balance and functional mobility [3,4,5,6,7,8,9], and the effect of D-hormone treatment (alfacalcidol or calcitriol) on risk of falls has been proven in several studies [1,2]. The low D-hormone serum levels observed with a creatinine clearance of <65 ml/min may also be one reason for the increased osteopenia and osteoporosis observed with low creatinine clearance by other authors [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8,9,30,31) For example, vitamin D status has been associated with cognitive function such as attention, which is involved in gait control in older adults. (32)(33)(34)(35)(36) Fast-pace walking is precisely considered as a more attention-demanding task than usual-pace walking, (23,36) which could explain in part the close positive association shown in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have investigated the risk factors for falls in the elderly [5,6,7]. Among others, vitamin D deficiency and/or low D-hormone (calcitriol/1,25(OH) 2 D 3 ), associated with a decrease of muscle strength [8,9,10,11], decreased balance [8,12,13], and loss of functional mobility [13,14], are more and more recognized to be important risk factors for falls in the elderly. Several recently published studies have shown that supplementation of vitamin D in vitamin D-deficient institutionalized women [15] and treatment with either calcitriol in osteopenic vitamin D-replete women [16] or alfacalcidol, a D-hormone prodrug, in a population of community-dwelling elderly non-vitamin D-deficient men and women [17] can significantly reduce frequency of falls [15,16,17] and number of fallers [17].…”
Section: Introductionmentioning
confidence: 99%